2015
DOI: 10.1371/journal.pntd.0004043
|View full text |Cite
|
Sign up to set email alerts
|

Re-assess Vector Indices Threshold as an Early Warning Tool for Predicting Dengue Epidemic in a Dengue Non-endemic Country

Abstract: BackgroundDespite dengue dynamics being driven by complex interactions between human hosts, mosquito vectors and viruses that are influenced by climate factors, an operational model that will enable health authorities to anticipate the outbreak risk in a dengue non-endemic area has not been developed. The objectives of this study were to evaluate the temporal relationship between meteorological variables, entomological surveillance indices and confirmed dengue cases; and to establish the threshold for entomolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(98 citation statements)
references
References 56 publications
(60 reference statements)
3
86
0
2
Order By: Relevance
“…In countries where dengue is endemic, mosquito activity was monitored for vector control interventions and to evaluate the effectiveness of control methods. Studies conducted in Taiwan indicated that mosquito abundance was a predictor of the dengue transmission risk [67] and that mosquito indices and climatic variables were early warning factors [68]. Herein, we found a positive association between container index and dengue transmission, suggesting that the mosquito population plays an important role in dengue fever transmission in central Vietnam.…”
Section: Discussionsupporting
confidence: 50%
“…In countries where dengue is endemic, mosquito activity was monitored for vector control interventions and to evaluate the effectiveness of control methods. Studies conducted in Taiwan indicated that mosquito abundance was a predictor of the dengue transmission risk [67] and that mosquito indices and climatic variables were early warning factors [68]. Herein, we found a positive association between container index and dengue transmission, suggesting that the mosquito population plays an important role in dengue fever transmission in central Vietnam.…”
Section: Discussionsupporting
confidence: 50%
“…HI, BI, CI and PI and dengue transmission/ dengue outbreak prediction[19], [20],whereas other reported that either of these indices or their combination has importance in prediction of the risk of dengue transmission/dengue outbreak[2123]. It has been suggested that Container Pupal Index and proportion of containers positive with pupae be taken the basis for vector surveillance and disease control [24].…”
Section: Discussionmentioning
confidence: 99%
“…aegypti, mosquito density and virus transmission are closely related, but at different spatial scales [57], with the scale to best consider dengue transmission still unclear. Although there has been some success correlating vector abundance or environmental factors with risk for dengue [58], other studies have shown poor correlation [59], particularly for urban areas with mosquitoes that breed in human-created habitat and thus depend less on environmental factors such as rainfall [60]. Percent human feeding and mosquito density data are needed to rigorously assess the thresholds and scales at which mitigations of mosquito abundance and human biting rates might be effective.…”
Section: Discussionmentioning
confidence: 99%